MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA CV. KUMBANG MAS JAYA - Muhamad Agus Teguh Herlambang; Suci Fitriana Pramudya Wardani; Rudi (Lembaga Penelitian & Pengabdian Masyarakat Sekolah Tinggi Ilmu KesehatanBrebes, 2021)
Background: The company will strive to achieve its goals effectively and efficiently. The advantages of a company can be achieved through several factors, one of these factors is the company's internal capabilities or through the company's resources. Human resources need motivation and performance discipline in order to develop their talents and change a monotonous mindset into an innovative soul, the role of a leader is the spearhead in changing the mindset of existing human resources. Methods: The research method used in this study is the causal association method and uses a quantitative approach. This research was conducted on CV. Kumbang Mas jaya directly to obtain data, implementation time in May-June 2021. The data analysis of this research is multiple linear regression analysis using the SPSS application. Result: Work motivation has a positive and significant influence on employee performance CV. Kumbang Mas Jaya is (∆R2) 0.265. Work discipline has a positive and significant effect on employee performance CV. Kumbang Mas Jaya is (∆R2) 0.320. Work motivation and work discipline simultaneously have an influence on employee performance CV. Kumbang Mas Jaya is (∆R2) 0.382. Conclusion: Motivation and discipline have a deep influence for someone to do their job, therefore they must be self-aware and willing to try to change themselves to become effective and efficient human resources and be proud of by all leaders and colleague. Efforts to increase work motivation and Employee performance can be improved by conducting more frequent training and efforts to improve work discipline are also carried out by applying penalties or sanctions for employees who violate company regulations.